Mastectomy and Physical Exercise - Jorge Luis Abreus Mora; Vivian Bárbara González Curbelo (Revista Finlay, 2024)
Important benefits have been shown when performing moderate-intensity physical activity after the diagnosis of breast cancer. Interventions must begin before, during and after the surgical intervention. It is recommended to take into account: the stage of the disease, the type of cancer, the physical condition, the possibility of reducing the volume or intensity of exercise; if not, you should start progressively, gradually increasing the intensity and duration of physical activity. Physical activity exercised regularly and with a certain intensity reduces the risk of tumor recurrence and mortality from breast cancer; it increases the quality of life, reduces the toxic effects of treatments, therefore, improves the prognosis of the disease.